Moro vowel harmony: implications for transparency and representations*. Issue 1 (5th May 2017) - Ritchart, Amanda; Rose, Sharon
Abstract : This paper describes and analyses the vowel-harmony system of the Kordofanian language Moro. Moro has a cross-height dominant-recessive raising harmony system in which high vowels and a central mid vowel trigger harmony, while peripheral mid vowels and a central low vowel are harmony targets. Schwas can co-occur with any of the vowels, appearing inert to harmony. Yet when schwas occur alone in a morpheme, some trigger harmony and some do not. We suggest that an original ATR-harmony system shifted to a height system via merger and centralisation, producing two distinct central vowels, rather than a single schwa. One vowel patterns with the higher vowels in triggering harmony, and the other patterns with the lower vowels. We also propose that a particle-based representation offers the best characterisation of the groupings of target and trigger vowels in the language.